Utilization of Lime Leaf (Citrus aurantilofia) Extract as an Eco-Friendly Alternative Strategy for the Management of Sitophilus zeamays - Debby Dijola Moniharapon; Evelin Tuhumuri; Mechiavel Moniharapon; Cindri Tasane (Pattimura University, 2026)
The maize weevil (Sitophilus zeamays) is a major postharvest pest that frequently damages stored grains, as evidenced by characteristic feeding perforations. The use of botanical insecticides represents an environmentally friendly alternative for pest management. One promising natural resource is lime leaf (Citrus aurantifolia). This study aimed to evaluate the effectiveness of lime leaf extract on the mortality of the maize weevil (Sitophilus zeamays). A laboratory-based experimental approach was employed using five dosage treatments (0 g as the control, 3 g, 8 g, 13 g, and 18 g), each replicated three times. Observations were conducted at 0, 12, 14, 16, and 18 hours after exposure. Data were analyzed using a two-way analysis of variance (two-way ANOVA) to simultaneously assess the effects of dosage and exposure time on pest mortality. The results indicated that lime leaf extract was effective as a botanical insecticide, with mortality rates increasing in proportion to both dosage and duration of exposure. The most effective treatment was 18 g, which resulted in the highest mortality rate of 98.34% after 18 hours. These findings suggest that lime leaf extract has strong potential for development as a botanical insecticide for sustainable and environmentally safe storage pest management.